Atribut Wisata, Pemasaran Berbasis Media Sosial, dan Kepuasan Wisatawan pada Pantai Lasiana Kupang - Maria, Maria; Ringa, Maria B; Adoe, Krysler K (Jurnal Ilmiah Aset, 2018)
Known as a superior tourist icon of Kupang, Lasiana Beach still keeps its management problems in its tremendous potential. The objectives of this research are: 1) To explore the existing tourist attraction attributes provided by the local government in the future for Lasiana Beach area; 2) Knowing the existence of tourist attractions, facilities and services, access to tourist destinations, and the prevailing prices related to the satisfaction of tourists at Lasiana Beach; 3) Knowing the level of satisfaction of domestic and foreign tourists who have experience with Lasiana Beach tourist area and its relation to available tourist attribute; and 4) Developing a conducive model of tourism attributes and their relationship to the satisfaction of tourists in the Lasiana Beach. This research is conducted by in-depth interview and FGD (Focus Group Discussion) by taking informants from foreign tourists, local district government and local community., Triangulation ofdata and examination of the validity of data directly by the Research Team. The result of this research is the model that is produced for the innovation on the attribute of a good tourist attraction, improvement of facility and service, improvement of accessibility and adjustment of price is expected to give guarantee of the satisfaction of tourist, especially followed by implementation of marketing strategy such as promotion service mix, especially media usage strategy advertising media such as social media based marketing with optimal budgeting to increase the rate of tourist arrivals to Lasiana Beach attractions.